Sam Gompers and the Expansion of the A.F. of L. Into Canada, 1882-1898 - Babcock, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1972)
In the 1890's Gompers began dreaming of an international federation of labor, and became increasingly anxious to assert hegemony over organized labor in Canada. At the same time, some Canadians hoped to transform the Trades Congress into a Canadian federation of labor which would doubtless absorb, in time, the international union locals in Canada. Largely because Trades Congress leaders felt compelled to rely upon the Federation for funds and organizers, aC. F. of L. never came to pass, and Gompers was free to pursue his continentalist designs. The famous Berlin decisions of 1902 were rather clearly foreshadowed by the end of 1898.